The Influence of Instagram Usage Motives towards Loneliness Among Undergraduate Students in the Jabodetabek Area - Gideon, Caleb Theophilus; Masinambow, Chrisvia Victory; Rorong, Putri Daniela Ekaristia; Putra, Wahyuda Abdia; Anthony, Nice Vyani; Siwabessy, Priska Eunike; Novanto, Yusak (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
Many emerging adults in Indonesia, especially those in Jabodetabek, often experience feelings of loneliness, which distorts social cognition and behavior. This study investigates the influence of Instagram usage motives on loneliness among undergraduate students in the Jabodetabek area. 112 students participated in this study, and a correlation matrix analysis and linear regression were used to analyze the data. The instruments used were the Instagram Motives Questionnaire (IMQ) and the UCLA Loneliness Scale version 3 (ULS-3). This quantitative cross-sectional study found a significant negative correlation between social impact seeking Instagram usage motive and loneliness (rho=-0.203, p=0.031). The results of the linear regression analysis found that only the social impact-seeking dimension had an influence of 7.1% on loneliness. This fact indicates that the motive of seeking social impact on Instagram is associated with lower subjective feelings of loneliness during the emerging adulthood period. In contrast, other dimensions of Instagram usage motives did not show a significant influence on loneliness. It is suggested to the participants that they do several other religious and social activities besides using Instagram on their social media to reduce their loneliness.